Ekspresi Anak-Anak Petani Tradisional Taram Dalam Lukisan - -, Hanafi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
The agricultural sector is a sector that has stratesis role in national economic development structure. This is a sector that does not get serious attention from the government in nation building. Ranging from protection, credit to none other policies that benefit the sector. Agricultural development programs that were never targeted goals even further plunges in the destruction of this sector, and also farming in Indonesia is still a lot that mengarap farm with traditional systems. When we look at the lives of farmers villages Taram Harau Sub District Fifty Cities of West Sumatra province rich in natural tones, surrounded by hills are fresh sounds, and also worked on his rice field farmers still use traditional tools. Taram seen from the way farmers work their fields, who are still using tools tradisioanal painstakingly family survival. There appears an impression that inspires the heart to express it in a painting, thus giving special value of the beholder. Painting to be made in this work, starts from the fact that occur in the environment around the residence and family home writer, born of a family of low income farmers. This situation prompted the authors to express their anxieties, pressures, and ketikberdayaan see the reality of what happened. In the work will be made only writer to express anxieties heart to see and feel what is happening within the family. Forms of his paintings are not made Ã¢â‚¬â€¹Ã¢â‚¬â€¹of natural background and activities of farmers in general, but only as an expression depicts peasant children with realist style, which is an imitation of a painting depicting the actual object.Â Keywords: expression of the kids, agriculture, economy.